Violência, violências: algumas de suas expressões em contos de Rubens Fonseca - Flores, Pablo Jamilk (2011)
The general aim in this work is to understand the violence phenomena represented in Literature, through the reading of some short stories of the Brazilian writer Rubem Fonseca. It is proposed to comprehend the violence portrait in the short stories by a sociological way, i.e. as one of the ways to understand the imbalance in the relation we-I, written by Nobert Elias, in one ―society composed by individuals‖, where men live in groups, although they think they are separated. In order to comprehend the presence of violence in literature, some of the author s main narratives which problematize the theme along the history. So, the selection of the short-story genre is done, and some of the main cases in which the violence theme appears is registered, since the fiction of great writers in the occidental canon until the fiction of Rubem Fonseca, a great centerpiece in the violence representation in the contemporary literature. Thus, a typology of the violence social types was built through a categorization of the Rubem Fonseca s characters who represent the contemporary social actors in the diegesis. This character typification allowed the violence in the contemporary social relations to be understood, deeply related to the daily experiences in big cities.